2008
DOI: 10.1111/j.1740-8261.2008.00428.x
|View full text |Cite
|
Sign up to set email alerts
|

Virtual Ct Otoscopy of the Middle Ear and Ossicles in Dogs

Abstract: Virtual otoscopy enables noninvasive 3D endoluminal imaging of the middle ear through postprocessing of computed tompgraphy (CT) data. A standardized imaging approach for the middle ear was established in six normal dogs in an attempt to optimize the clinical application and student education. High-resolution CT data were obtained. Virtual otoscopic images of the middle ear cavity and ossicles were generated using commercially available software. The views of the four different directions (the ear canal, tympa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 17 publications
2
8
0
2
Order By: Relevance
“…Although a topographical image produced by VO cannot depict color shades of the canal itself, which can be detected by fiberoptic endoscopy [12,26], VO has been widely investigated in human medicine as a supplement to diagnostic imaging and surgical planning [8,12,18,25]. In veterinary medicine, the utility of VO for examining the inside ear was recently assessed in normal dogs [6]. No study, however, has reported on the application of VO in dogs with an infectious ear disease such as otitis media.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although a topographical image produced by VO cannot depict color shades of the canal itself, which can be detected by fiberoptic endoscopy [12,26], VO has been widely investigated in human medicine as a supplement to diagnostic imaging and surgical planning [8,12,18,25]. In veterinary medicine, the utility of VO for examining the inside ear was recently assessed in normal dogs [6]. No study, however, has reported on the application of VO in dogs with an infectious ear disease such as otitis media.…”
Section: Discussionmentioning
confidence: 99%
“…VO of the middle ear is generally still not used in veterinary medicine. Previously, VO alone was investigated as a means for generating anatomic reference images of the canine middle ear in normal dogs [6]. However, no information on VO images has been reported in veterinary medicine.…”
Section: Introductionmentioning
confidence: 99%
“…O uso de simuladores vem crescendo para as partes delicadas da anatomia humana, como o ouvido. Partes do corpo muito pequenas a "olho nu" são reproduzidas e aumentadas pela computação, o que permite uma visualização não conseguida com uso de peças anatômicas (os cadáveres) (19) .…”
Section: Ensino: Otoscopia Virtual Para Indicar Lesões E Para Ensinarunclassified
“…A endoscopia virtual permite inspeção visual da finas estruturas do osso temporal e não necessita de mais dados do que a tomografia computadorizada de rotina, mas fornece informação topográfica 3D virtual endoscópica. Tem sido usada para diagnóstico, planejamento cirúrgi-co, e o ensino nas escolas (19) .…”
Section: Exames: Otoscopia Virtualunclassified
“…Some of the studies regarding ear morphology of animals were carried out to reveal functional roles of ear especially in fossorial rodents (Lange et al, 2004;Lange and Burda, 2005;Mason, 2006), and some other studies (Pracy et al, 1998;Seibel et al, 2006a;Borin et al, 2008) made morphological comparisons to humans. To understand the anatomic problems and vascular diseases, certain techniques like radiography, ultrasonography, computed tomography, and magnetic resonance were applied to animals as well, and carnivores (e.g., cats, dogs) were frequently used for this purpose (Allgoewer et al, 2000;Russo et al, 2002;Eom et al, 2008).…”
mentioning
confidence: 99%